Amelioration of Sugar Mill Effluent Polluted Soil Using Microbial Isolates and its Response on Paddy - S.M. Muthukkaruppan, Sajani Samuel* and (Current Botany, 2011)
<span style="font-family: ";Arial Narrow";,";sans-serif";; font-size: 10pt; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Sugar mills play a major role in polluting the water bodies and land by discharging a large amount of wastewater as effluent. The continuous use of these effluents harmfully affects the crops when used for irrigation. As a result, a higher amount of various elements get deposited in the soil and make them polluted. Since this polluted soil reduces both the crop production as well as the soil properties, it was decided to give some bioremediation measures by treating the soil with microbial isolates. The physico- chemical analysis of the sugar mill polluted soils revealed that they are toxic in nature because they contain higher amount of micronutrients and macronutrients, organic and inorganic chemicals and heavy metals. In order to bioremediate the soil quality, PGPR and fungal isolates (Bacillus spp + Pseudomonas spp and Aspergillus niger + Penicillium spp) were cultured in the soil for 60 days. After that, the various soil properties were analysed and good percentage of pollutant reduction was observed. Germination studies were conducted in bioremediated soil and best germination was noticed under bioremediated soil when compared with polluted soil.